Rekontekstualisasi Pemikiran Marx, Weber, dan Durkheim dalam Kerangka Dakwah Sosial Keagamaan - Ula, Umi Nailul; Firdaus, Yuliatul; Arifin, Imamul; Siswanto, Ali Hasan (IDARI: Jurnal Manajemen Dakwah, 2025)
This study aims to recontextualize the classical sociological theories of Karl Marx, Max Weber, and Émile Durkheim within the framework of dakwah (Islamic propagation) to address the theoretical limitations often dominated by normative-theological approaches. The research focuses on three main questions: (1) the relevance of classical theories when applied to contemporary dakwah phenomena; (2) the reasons behind the epistemological gap in dakwah studies caused by the lack of critical analysis; and (3) the construction of a new conceptual framework through the synthesis of classical theory and dakwah praxis for advancing the religious social sciences. Using a conceptual research design and critical analytical approach, this study draws from primary sources such as the original works of Marx, Weber, and Durkheim, and secondary sources consisting of Scopus- and WoS-indexed journal articles from 2015–2024 discussing dakwah, Islamic communication, and classical sociology. The methodology integrates critical interpretation, comparative analysis, and framework synthesis to produce a comprehensive model. The findings demonstrate that Marx’s theory contextualizes dakwah as a domain of ideological struggle and class relations; Weber’s perspective elucidates authority, rationalization, and bureaucratization within dakwah institutions; and Durkheim’s approach highlights the role of dakwah in maintaining social solidarity and collective morality. The study concludes that the integration of these classical perspectives formulates Critical-Integrative Dakwah Studies, a new paradigm that views dakwah as both a religious and transformative social praxis. This epistemological synthesis expands the horizon of religious social sciences and promotes dialogue between Western and Islamic intellectual traditions.